INDIKATOR PENYEBAB KETIMPANGAN PEREKONOMIAN KABUPATEN/KOTA DI PROVINSI ACEH - Fajri Hadi (Universitas Teuku Umar, 2018)
This study was to analyze the growth economic and disparited between districts / cities in Aceh province. To see this inequality Aceh GDP data was used to the model and typology Klassen Williamson Index. The results showed that the rate coefficient of inequality of growth economic in the Province of Aceh has improved. This is indicated by the high coefficient of inequality from 2004 to 2014. Government spending and the number of people positive and significant effect in increasing the index of inequality across districts / cities in Aceh province. 51.09 percent of the variation of the index of income inequality can be explained by government spending and population, while the remaining 48.91 percent is explained by other factors outside the model. Williamson index analysis results showed in the district / city having a very high inequality in 2008 and continues to grow so that in the year 2014 fell limp below average although still at the level of inequality of growth with a high index, but were able to show better development, for example Aceh Barat Daya district in 2008 had a very high inequality with coeficien index at 0,862 and further declined in 2010 with the index of inequality for 0,761 coeficien index(IW) is below the average. To reduce the level of inequality between regions in the province of Aceh in the future, the Government of Aceh need to increase spending on capital expenditures for the Central Region and the South West and the creation of employment for encourage the growth of regional economic.Keywords: disparities, government expenditure, growth economic.